DINAMIKA HUKUM ISLAM MASA MODERN DAN PROBLEMATIKANYA: SYARI’AH DAN DASAR-DASAR HAK ASASI MANUSIA (HAM) - Herfin Fahri (Al Hikmah: Jurnal Studi Keislaman, 2015)
The concept of human rights contained in the Universal Declaration is the product of an era that is inseparable from the influence of the historical, ideological, post-second world war intellectual background. Therefore, the concept of human rights, more or less, is the result of cultural fusion after the Western secular Enlightenment that is not grounded in religious principles. Regarding the concept of human rights as expressed in the Universal Declaration, some have accepted without reservation on the ground that the concept of human rights they have is in accordance with religious teachings. Conversely, some have considered that the basic principles of the Declaration is from the Western secular cultures that tend to put aside religious values. The third is the position of the moderates who take a cautious stance for accepting it with some changes and modifications.